Crisis of the user charges in the Argentine Republic: reflections in light of the jurisprudence of Peru, Uruguay and Brazil - Luna Requena, Álvaro Carlos (2014)
The article sets out that argentinean municipalities are legally banned from raising taxes, but are allowed to levy user charges for specific services. Nevertheless, such limitation is overlooked by the municipalities by means of introducing the “ability top ay” principle within the structure of the taxable base of said user charges. The author concludes that such mechanism distorts the user charge, altering its essence, with the result of transforming it into a mere tax, with the resulting violation of the current legislation.The author critically reviews argentinean case law that has given grounds to such a fiscal deviation and –in order to make his point- compares it with jurisprudence registered on this issue by the Supreme Courts of Peru, Brazil and Uruguay. Such comparison evidences that, if argentinean courts were to apply the criteria said of those Supreme Courts, almost every user charge in Argentina would have to be declared unconstitutional.